2019
DOI: 10.1111/cts.12616
|View full text |Cite
|
Sign up to set email alerts
|

Does In Vitro Cytochrome P450 Downregulation Translate to In Vivo Drug‐Drug Interactions? Preclinical and Clinical Studies With 13‐cis‐Retinoic Acid

Abstract: All‐trans‐retinoic acid (atRA) downregulates cytochrome P450 (CYP)2D6 in several model systems. The aim of this study was to determine whether all active retinoids downregulate CYP2D6 and whether in vitro downregulation translates to in vivo drug–drug interactions (DDIs). The retinoids atRA, 13cisRA, and 4‐oxo‐13cisRA all decreased CYP2D6 mRNA in human hepatocytes in a concentration‐dependent manner. The in vitro data predicted ~ 50% decrease in CYP2D6 activity in humans after dosing with 13cisRA. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 30 publications
2
59
0
Order By: Relevance
“…In plasma, the fraction of at RA bound is >0.99, [ 11 ] likely bound to albumin [ 1 , 33 ]. Pregnancy is associated with a decrease in albumin concentrations [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In plasma, the fraction of at RA bound is >0.99, [ 11 ] likely bound to albumin [ 1 , 33 ]. Pregnancy is associated with a decrease in albumin concentrations [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin A bioactivity is attributed to the metabolite all-trans -retinoic acid ( at RA), while other metabolites such as 13- cis -retinoic acid (13 cis RA), and the downstream metabolite of 13 cis RA, 4-oxo-13- cis -retinoic acid (4oxo13 cis RA) are also present in circulation and tissues in humans [ 2 ]. These metabolites circulate at lower concentrations than retinol [ 9 ] and bind to albumin [ 1 , 10 ] such that <0.001% circulates as the free form [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wang and colleagues report in vitro downregulation of CYP3A4 mRNA by carfilzomib in human hepatocytes in vitro, which did not affect midazolam pharmacokinetics in patients with cancer (AUC 0-' ratio [least squares mean (90% geometric CI) 108.2 (94.1-124)]) (Wang et al, 2013). Conversely, it was shown that weak induction of CYP3A-mediated midazolam clearance by the retinoid compounds was indeed predictable based on in vitro studies (Stevison et al, 2019). These studies again highlight the currently unreliable prediction of in vivo DDIs from in vitro data for CYP induction and/or downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Because there was no effect of multiple doses of 200 mg abemaciclib Q12H on dextromethorphan [AUCR 0.976 (0.805,1.18)], both the in vitro induction and downregulation appear to be false positives. The ability to predict in vivo CYP2D6 induction from in vitro studies is mixed: Sager et al (2017) successfully predicted CYP2D6-mediated DDIs for bupropion based on simultaneous CYP2D6 inhibition and induction, but in vitro CYP2D6 downregulation by retinoids identified by Stevison et al (2019) did not translate into the clinic. The CYP1A2 substrate caffeine exhibited statistically significant increases in AUC, but the analysis was confounded by evidence of noncompliance with the dietary restriction of caffeine.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, reduced expression of non-specific RA-degrading cytochromes may provide a mechanism for increased at-RA serum levels in clozapine-treated subjects. On the other hand, recent in vitro evidence demonstrates the downregulation of CYP2D6 mRNA upon stimulation with retinoids [ 76 ], which suggests that reduced levels of CYP2D6 in clozapine patients may also be a consequence of increased RA-signaling. The results must, however, be interpreted with caution, particularly because little is known about the role and functional implications of altered blood-cell-based mRNA expression of CYP450 isozymes.…”
Section: Discussionmentioning
confidence: 99%